ChemInform Abstract: Oxindole Alkaloids from the Fungus Penicillium commune DFFSCS026 Isolated from Deep‐Sea‐Derived Sediments. Issue 22 (15th May 2015) - Xu, Xinya; Zhang, Xiaoyong; Nong, Xuhua; Wei, Xiaoyi; Qi, Shuhua
Abstract: isolation, structure determination and biological activity of nine new oxindole alkaloids, cyclopiamides B—J (I)—(V)